High-homogeneity cement paste as well as preparation method and application thereof
By using composite superdispersant and modified microbeads in cement slurry, combined with appropriate stirring speed, the problem of high requirements for cement slurry homogeneity and water-cement ratio is solved, and efficient cement slurry dispersion and flow are achieved. Improved performance reduces the risk of energy waste and equipment damage.
Patent Information
- Application Number
- CN202411472934.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-07
AI Technical Summary
When the prior art improves the homogeneity of cement slurry, relying on high-speed stirring leads to energy waste and equipment damage, and is difficult to maintain. In some cases, the water-cement ratio requirements are small, making it more difficult to uniformly disperse the cement slurry.
Compound superdispersant, including polycarboxylic acid water reducing agent, retarder and defoaming agent, combined with the design of stirring speed, improve the dispersion of cement particles by reducing the size of flocculants and reducing the degree of flocculation, and through modification The beads and surfactants prevent agglomeration and achieve high homogeneity of the cement slurry.
It effectively improves the fluidity and dispersion of cement slurry, reduces the waste of cement and water, and improves the efficiency and service life of the mixing equipment, which is of practical and economic significance.
Smart Images

Figure CN119263686A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based materials, and in particular to a highly homogeneous cement slurry and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background section is intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] my country's infrastructure construction is booming, and the requirements for the quality and performance of cement concrete are constantly increasing. Whether the cement slurry is evenly dispersed directly affects the quality and production efficiency of concrete, especially in certain specific cases where concrete is required to have higher strength, which requires a smaller water-cement ratio, making the uniform dispersion of cement slurry more difficult.
[0004] At present, the main way to improve the homogeneity of cement paste is through high-speed stirring or improving cement paste stirring technology. This method mainly releases the encapsulated water in the flocculent particles through high-speed stirring, thereby achieving the effect of increasing the amount of water. Secondly, there are also cement paste mixing equipment with various structures and models designed according to different mixing principles. These methods have a positive effect on improving the homogeneity of the paste, but only increasing the stirring speed will not only cause energy waste, but also damage the equipment to varying degrees, making it difficult to maintain and having a short service life. Summary of the invention
[0005] In view of the deficiencies in the prior art, a first object of the present invention is to provide a highly homogeneous cement slurry.
[0006] The second object of the present invention is to provide a method for preparing the above-mentioned highly homogeneous cement paste. The present invention aims at the agglomeration characteristics of cement particles, and can effectively solve the agglomeration problem of cement particles by using a composite hyperdispersant combined with stirring speed, and is also conducive to reducing the waste of cement and water, which has practical and economic significance.
[0007] The third object of the present invention is to provide an application of the above-mentioned highly homogeneous cement slurry.
[0008] To achieve the above object, the present invention adopts the following technical solution: A polycarboxylate water reducer comprises, by weight, 4.0-8.0 parts of sodium methacrylic acid sulfonate, 300-400 parts of isopentanol polyoxyethylene ether and 20-40 parts of acrylic acid.
[0009] Furthermore, the preparation method comprises the following steps: (1) Add ammonium persulfate, sodium methyl methacrylate sulfonate and isopentanol polyoxyethylene ether to deionized water to prepare solution A, and place the solution in a four-necked flask for later use; (2) Add ascorbic acid and ferrous sulfate to deionized water to prepare solution B, and place it in a conical flask for later use; (3) Add acrylic acid to deionized water to prepare solution C, and place it in a conical flask for later use; (4) 25% of the mass of the solution B obtained in step (2) and 30% of the mass of the solution C obtained in step (3) are added to the solution A obtained in step (1), the temperature of the moderated solution is raised to 35° C., and the remaining solution B obtained in step (2) and the solution C obtained in step (3) are added dropwise at the same time. The addition time of solution B and solution C is 120 min and 140 min, respectively. After the addition of solution C is completed, the mixture is stirred for 30 min to obtain the polycarboxylate water-reducing agent.
[0010] Furthermore, in step (1), the oxidant is ammonium persulfate; The molecular weight of the isopentanol polyoxyethylene ether is 4000; According to the mass ratio, the proportion of ammonium persulfate, sodium methyl methacrylate sulfonate, isopentanol polyoxyethylene ether and deionized water is (5.0~9.0): (4.0~8.0): (300~400): (300~500).
[0011] Furthermore, in step (2), the mass ratio of ascorbic acid, ferrous sulfate and deionized water is (0.3-1.2): (0.2-0.6): (55-105).
[0012] Furthermore, in step (3), the mass ratio of acrylic acid to deionized water is (20-40): (50-90); In terms of mass ratio, the ratio of ammonium persulfate in step (1), ascorbic acid in step (2) and acrylic acid in step (3) is (5.0-9.0):(0.3-1.2):(20-40).
[0013] A highly homogeneous cement slurry is obtained by mixing cement, modified microspheres, mineral powder, water and a composite superdispersant through stirring, and is composed of the following parts by weight: 40-60 parts of cement, 20-40 parts of modified microspheres, 10-30 parts of mineral powder, 22-28 parts of water, and 1-2 parts of a composite superdispersant.
[0014] Furthermore, the highly homogeneous cement slurry is composed of 43-55 parts of cement, 24-36 parts of modified microspheres, 12-27 parts of mineral powder, 25-27 parts of water, and 1-2 parts of composite hyperdispersant.
[0015] Furthermore, the cement is silicate cement.
[0016] Furthermore, the microbeads are spherical particles with a particle size of 0.1-5.0 μm, and after being mixed with a modifier, modified microbeads are obtained.
[0017] Furthermore, the particle size of the microbeads is 0.1-3.0 μm.
[0018] Furthermore, the modifier is Wenlun rubber and sodium dodecyl sulfate, and the mixing ratio of the two is 1:3.
[0019] Furthermore, the composite hyperdispersant is composed of a polycarboxylic acid water reducer, a retarder and a defoamer, wherein the ratio of the polycarboxylic acid water reducer, the retarder and the defoamer is (90-96): (2-8): (0.5-1).
[0020] Furthermore, the ratio of polycarboxylic acid water reducer, retarder and defoamer is (92~95):(3~7):(0.6~1).
[0021] Furthermore, the molecular weight of the isopentanol polyoxyethylene ether is 4000, the oxidant is ammonium persulfate, the reducing agent is ferrous sulfate and ascorbic acid, and sodium methacrylate sulfonate is both a raw material for polycarboxylic acid water reducer to regulate the adsorption characteristics of the main chain and a chain transfer agent required for synthesizing the polycarboxylic acid water reducer.
[0022] Furthermore, the retarder is two of white sugar, sodium gluconate, citric acid, and potassium sodium tartrate, and the defoamer is a polyether-modified polysiloxane defoamer. Preferably, the retarder is two of sodium gluconate, citric acid, and potassium sodium tartrate.
[0023] Furthermore, the stirring speed is composed of stages, slow stirring at 60 r / min for 10 s, and then fast stirring at 1650 r / min for 25 s.
[0024] The application of the above-mentioned high-homogeneity cement slurry, the high-homogeneity cement slurry can be used in the construction field.
[0025] Beneficial effects: (1) The superdispersant composed of a polycarboxylic acid water reducer, a retarder and a defoamer in the present invention destroys the network structure floccules produced by cement slurry hydration under the action of the steric hindrance and electrostatic repulsion of the water reducer, effectively reducing the flocculation degree and floccules size of the freshly mixed cement slurry, thereby improving the dispersibility of the particles and the fluidity of the slurry. At the same time, with the increase of the stirring speed, the water contained in the flocculent particles is released, thereby improving the homogeneity of the cement slurry.
[0026] (2) The microbeads in the present invention are modified by composite of Weinlun rubber and sodium dodecyl sulfate. Weinlun rubber is composed of high molecular weight polysaccharide substances, and contains multiple carboxyl and hydroxyl groups in its molecular structure. The carboxyl group can form hydrogen bonds or other interactions with the surface of the microbeads, so that the Weinlun rubber molecules are adsorbed on the surface of the microbeads; the hydroxyl group increases the hydrophilicity of the molecule, which helps to form a stable dispersion system in the cement slurry. These characteristics enable Weinlun rubber to effectively disperse the microbeads and prevent them from agglomerating, thereby improving the uniformity and stability of the microbeads in the cement slurry. Sodium dodecyl sulfate forms a coating layer by adsorbing on the surface of the microbead particles, so that the surface of the microbeads has the same charge. This surfactant coating generates electrostatic repulsion between the microbeads, preventing agglomeration or deposition, thereby improving the dispersibility and stability of the microbeads in the cement slurry.
[0027] (3) The present invention is beneficial to the dispersion of cement slurry particles by designing the stirring speed and cooperating with the composite superdispersant. It can improve the stirring quality and efficiency of the stirring equipment while reducing the waste of cement and water, and has practical and economic significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention, and do not constitute an improper limitation of the present invention.
[0029] Figure 1 A microscope image of a highly homogeneous cement slurry prepared in the first embodiment; Figure 2 A microscopic image of a highly homogeneous cement slurry prepared in the second embodiment; Figure 3 This is a microscope image of the highly homogeneous cement slurry prepared in the first comparative example; Figure 4 This is a microscope picture of the highly homogeneous cement slurry prepared in the second comparative example. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0031] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If not otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in the present invention are for demonstration purposes only. The present invention is further described according to the accompanying drawings and specific embodiments of the specification.
[0032] First embodiment 1. Prepare polycarboxylate water reducer, the preparation steps are: (1) Add ammonium persulfate, sodium methacrylate sulfonate and isopentanol polyoxyethylene ether to deionized water to prepare solution A, and place the solution A into a four-necked flask for later use; the mass ratio of ammonium persulfate, sodium methacrylate sulfonate, isopentanol polyoxyethylene ether and deionized water is 7.2:7.9:400:310; (2) Add ascorbic acid and ferrous sulfate to deionized water to prepare solution B, and place it in a conical flask for later use; the mass ratio of ascorbic acid, ferrous sulfate and deionized water is 0.7:0.2:100; (3) Add acrylic acid to deionized water to prepare solution C, and place it in a conical flask for later use; the mass ratio of acrylic acid to deionized water is 31:60; (4) 25% of the mass of the solution B obtained in step (2) and 30% of the mass of the solution C obtained in step (3) are added to the solution A obtained in step (1) at one time. When the temperature of the solution in the four-necked flask rises to 35° C., the solution B obtained in step (2) and the solution C obtained in step (3) are added dropwise at the same time. The addition time of the solution B and the solution C is 120 min and 140 min, respectively. After the addition of the solution C is completed, the mixture is stirred for 30 min to obtain a polycarboxylate water reducer. In terms of mass ratio, the ratio of ammonium persulfate in step (1), ascorbic acid in step (2) and acrylic acid in step (3) is 7.2:0.7:31.
[0033] Polycarboxylate water reducer is composed of isopentanol polyoxyethylene ether, sodium methacrylate sulfonate and acrylic acid, and the molar ratio of the three is 1:0.5:4.3. The molecular weight of isopentanol polyoxyethylene ether is 4000, the oxidant is ammonium persulfate, and the reducing agent is ferrous sulfate and ascorbic acid. Sodium methacrylate sulfonate is both the raw material of polycarboxylate water reducer to regulate the adsorption characteristics of the main chain and the chain transfer agent for synthesizing polycarboxylate water reducer, which is obtained by free radical polymerization.
[0034] 2. Preparation of composite hyperdispersant The composite superdispersant is composed of a polycarboxylic acid water reducer, a sodium gluconate retarder, a citric acid retarder and a polyether modified polysiloxane defoamer, wherein the ratio of the polycarboxylic acid water reducer, the retarder and the defoamer is 92:5:0.6.
[0035] 3. Preparation of Modified Microbeads The microbeads and the modifier are mixed by high-speed stirring. The modifier is Wenlun rubber and sodium dodecyl sulfate. The mixing ratio of the two is 1:3 to obtain modified microbeads.
[0036] 4. Preparing a highly homogeneous cement slurry comprises the following steps: Portland cement, modified microspheres with a particle size of 1.0 μm, mineral powder, water, and composite superdispersant were mixed in proportion, first stirred at 60 r / min for 10 s, and then stirred at 1650 r / min for 25 s to obtain a highly homogeneous cement slurry; in terms of mass ratio, the ratio of Portland cement, modified microspheres, mineral powder, water, and composite superdispersant was 44:30:21:24:1.3.
[0037] Second embodiment 1. Prepare polycarboxylate water reducer, the preparation steps are: (1) Add ammonium persulfate, sodium methacrylate sulfonate and isopentanol polyoxyethylene ether to deionized water to prepare solution A, and put it into a four-necked flask for later use; according to the mass ratio, the ratio of ammonium persulfate, sodium methacrylate sulfonate, isopentanol polyoxyethylene ether and deionized water is 5.0:5.9:300:300; (2) Add ascorbic acid and ferrous sulfate to deionized water to prepare solution B, and place it in a conical flask for later use; the mass ratio of ascorbic acid, ferrous sulfate and deionized water is 0.3:0.2:55; (3) Add acrylic acid to deionized water to prepare solution C, and place it in a conical flask for later use; the mass ratio of acrylic acid to water is 23.2:50; (4) 25% of the mass of the solution B obtained in step (2) and 30% of the mass of the solution C obtained in step (3) are added to the solution A at one time. When the temperature of the solution in the four-necked flask rises to 35° C., the solution B obtained in step (2) and the solution C obtained in step (3) are added dropwise at the same time. The addition time of the solution B and the solution C is 120 min and 140 min, respectively. After the addition of the solution C is completed, the mixture is stirred for 30 min to obtain a polycarboxylate water-reducing agent.
[0038] In terms of mass ratio, the ratio of ammonium persulfate in step (1), ascorbic acid in step (2) and acrylic acid in step (3) is 5.0:0.3:23.2.
[0039] Polycarboxylate water reducer is composed of isopentanol polyoxyethylene ether, sodium methacrylate sulfonate and acrylic acid, and the molar ratio of the three is 1:0.5:4.3. The molecular weight of isopentanol polyoxyethylene ether is 4000, the oxidant is ammonium persulfate, and the reducing agent is ferrous sulfate and vitamins. Sodium methacrylate sulfonate is both the raw material of polycarboxylate water reducer to regulate the adsorption characteristics of the main chain and the chain transfer agent for synthesizing polycarboxylate water reducer, which is obtained by free radical polymerization.
[0040] 2. Preparation of composite hyperdispersant The composite superdispersant is composed of a polycarboxylic acid water reducer, a sodium gluconate slow-release agent, a citric acid retarder and a polyether modified polysiloxane defoamer, wherein the ratio of the polycarboxylic acid water reducer, the retarder and the defoamer is 90:2:0.5.
[0041] 3. Preparation of modified microbeads: The microbeads and the modifier are mixed by high-speed stirring. The modifier is Wenlun rubber and sodium dodecyl sulfate. The mixing ratio of the two is 1:3 to obtain modified microbeads.
[0042] 4. Preparing a highly homogeneous cement slurry comprises the following steps: After mixing silicate cement, modified microspheres with a particle size of 0.1 μm, mineral powder, water and composite superdispersant in proportion, the mixture was stirred at 60 r / min for 10 s and then at 1650 r / min for 25 s to obtain a highly homogeneous cement slurry; in terms of mass ratio, the ratio of silicate cement, modified microspheres, mineral powder, water and composite superdispersant was 40:20:10:22:1.
[0043] Third embodiment 1. Prepare polycarboxylate water reducer, the preparation steps are: (1) Add ammonium persulfate, sodium methacrylate sulfonate and isopentanol polyoxyethylene ether to deionized water to prepare solution A, and place the solution A in a four-necked flask for later use; the mass ratio of ammonium persulfate, sodium methacrylate sulfonate, isopentanol polyoxyethylene ether and deionized water is 7.2:7.9:400:310; (2) Add ascorbic acid and ferrous sulfate to deionized water to prepare solution B, and place it in a conical flask for later use; the mass ratio of ascorbic acid, ferrous sulfate and deionized water is 0.7:0.2:100; (3) Add acrylic acid to deionized water to prepare solution C, and place it in a conical flask for later use; the mass ratio of acrylic acid to water is 31:60; (4) 25% of the mass of the solution B obtained in step (2) and 30% of the mass of the solution C obtained in step (3) are added to the solution A at one time. When the temperature of the solution in the four-necked flask rises to 35° C., the solution B obtained in step (2) and the solution C obtained in step (3) are added dropwise at the same time. The addition time of the solution B and the solution C are 120 min and 140 min, respectively. After the addition of the solution B is completed, the mixture is stirred for 30 min to obtain a polycarboxylate water-reducing agent.
[0044] In terms of mass ratio, the ratio of ammonium persulfate in step (1), ascorbic acid in step (2) and acrylic acid in step (3) is 7.2:0.7:31.
[0045] Polycarboxylate water reducer is composed of isopentanol polyoxyethylene ether, sodium methacrylate sulfonate and acrylic acid, and the molar ratio of the three is 1:0.5:4.3. The molecular weight of isopentanol polyoxyethylene ether is 4000, the oxidant is ammonium persulfate, and the reducing agent is ferrous sulfate and vitamins. Sodium methacrylate sulfonate is both the raw material of polycarboxylate water reducer to regulate the adsorption characteristics of the main chain and the chain transfer agent for synthesizing polycarboxylate water reducer, which is obtained by free radical polymerization.
[0046] 2. Preparation of composite hyperdispersant The composite superdispersant is composed of a polycarboxylic acid water reducer, a sodium gluconate slow-release agent, a citric acid retarder and a polyether modified polysiloxane defoamer, wherein the ratio of the polycarboxylic acid water reducer, the retarder and the defoamer is 96:8:1.
[0047] 3. Preparation of modified microbeads: The microbeads and the modifier are mixed by high-speed stirring. The modifier is Wenlun rubber and sodium dodecyl sulfate. The mixing ratio of the two is 1:3 to obtain modified microbeads.
[0048] 4. Preparing a highly homogeneous cement slurry comprises the following steps: After mixing silicate cement, modified microspheres with a particle size of 0.1 μm, mineral powder, water and composite super dispersant in proportion, the mixture was stirred at 60 r / min for 10 s and then at 1650 r / min for 25 s to obtain a highly homogeneous cement slurry; in terms of mass ratio, the ratio of silicate cement, modified microspheres, mineral powder, water and composite super dispersant was 60:40:30:28:2.
[0049] The first comparison 1. Prepare polycarboxylate water reducer, the steps are the same as step 1 of the first embodiment.
[0050] 2. Prepare the composite hyperdispersant, the steps are the same as step 2 of the first embodiment.
[0051] 3. Prepare highly homogeneous cement slurry. The steps are different from those of the first embodiment 4 in that the cement slurry consists of cement, microspheres, mineral powder, water, and a composite hyperdispersant, that is, the microspheres are not modified.
[0052] The second comparison 1. Prepare the composite hyperdispersant. The step is different from step 2 of the first embodiment in that the composite hyperdispersant is composited by a commercially available common polycarboxylic acid water reducer, a retarder, and a defoamer.
[0053] 2. Prepare modified microbeads, the steps are the same as step 3 of the first embodiment.
[0054] 3. Prepare highly homogeneous cement slurry, the steps are the same as step 4 of the first embodiment.
[0055] The third comparison 1. Prepare polycarboxylate water reducer, the steps are the same as step 1 of the first embodiment.
[0056] 2. Prepare the composite hyperdispersant, the steps are the same as step 2 of the first embodiment.
[0057] 3. Prepare modified microbeads, the steps are the same as step 3 of the first embodiment.
[0058] 4. Prepare highly homogeneous cement slurry. The steps are different from those of the first embodiment 4 in that the stirring process is slow stirring at 60 r / min for 10 s, without fast stirring.
[0059] Performance Testing According to the national standard GB / T 8077-2023 “Test method for homogeneity of concrete admixtures”, the fluidity of the highly homogeneous cement pastes prepared in the examples and comparative examples was measured, and the results are shown in Table 1.
[0060] Table 1 Test results of fluidity of high homogeneous cement paste The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A polycarboxylate water reducer, characterized in that: In terms of weight percentage, the polycarboxylate water-reducing agent comprises: 4.0-8.0 parts of sodium methacrylic acid sulfonate, 300-400 parts of isopentanol polyoxyethylene ether and 20-40 parts of acrylic acid.
2. The method for preparing the polycarboxylate water-reducing agent according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Adding an oxidant, sodium methacrylate sulfonate and isopentanol polyoxyethylene ether to deionized water to prepare solution A for later use; (2) Add ascorbic acid and ferrous sulfate to deionized water to prepare solution B for later use; (3) Adding acrylic acid to deionized water to prepare solution C for later use; (4) 25% of the mass of the solution B obtained in step (2) and 30% of the mass of the solution C obtained in step (3) are added to the solution A obtained in step (1), the temperature is raised to 35° C., and the remaining solution B obtained in step (2) and the solution C obtained in step (3) are added dropwise at the same time. The addition time of solution B and solution C is 120 min and 140 min, respectively. After the addition of solution C is completed, the mixture is stirred for 30 min to obtain the polycarboxylate water-reducing agent.
3. The preparation method according to claim 2, characterized in that: In step (1), the mass ratio of the oxidant, sodium methacrylate sulfonate, isopentanol polyoxyethylene ether and deionized water is (5.0-9.0): (4.0-8.0): (300-400): (300-500), the oxidant is ammonium persulfate, and the molecular weight of the isopentanol polyoxyethylene ether is 4000; In step (2), the mass ratio of ascorbic acid, ferrous sulfate and deionized water is (0.3-1.2): (0.2-0.6): (55-105); In step (3), the mass ratio of acrylic acid to deionized water is (20-40):(50-90); The mass ratio of the oxidant in step (1), the ascorbic acid in step (2) and the acrylic acid in step (3) is (5.0-9.0):(0.3-1.2):(20-40).
4. A highly homogeneous cement slurry, characterized in that: According to the mass ratio, the highly homogeneous cement paste comprises: 40-60 parts of cement, 20-40 parts of modified microspheres, 10-30 parts of mineral powder, 22-28 parts of water, and 1-2 parts of composite superdispersant; The composite superdispersant is composed of the polycarboxylic acid water reducer according to claim 1, a retarder and a defoamer.
5. The highly homogeneous cement slurry according to claim 4, characterized in that: The mass ratio of the polycarboxylic acid water reducer, retarder and defoamer is (90-96): (2-8): (0.5-1).
6. The highly homogeneous cement slurry according to claim 4, characterized in that: The cement is Portland cement; The specific surface area of the mineral powder is 450 m 2 / kg; The modified microbeads are spherical particles with a particle size of 0.1-5.0 μm.
7. The highly homogeneous cement slurry according to claim 4, characterized in that: The modified microbeads are composed of a modifier, namely, Wenlun rubber and sodium dodecyl sulfate, in a mass ratio of 1:
3.
8. The highly homogeneous cement slurry according to claim 7, characterized in that: The retarder is any two of white sugar, sodium gluconate, citric acid and potassium sodium tartrate; The defoamer is a polyether-modified polysiloxane defoamer.
9. The method for preparing a highly homogeneous cement slurry according to any one of claims 4 to 8, characterized in that: The preparation method comprises the following steps: After cement, modified microspheres, mineral powder, water and composite superdispersant were mixed, the mixture was first stirred at 60 r / min for 10 s and then stirred at 1650 r / min for 25 s to obtain the highly homogeneous cement slurry.
10. The use of the highly homogeneous cement slurry according to claim 4, characterized in that: The highly homogeneous cement slurry is used in the field of construction.